2022
DOI: 10.1007/s10995-021-03305-1
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Providers Perceptions About Preconception Care in Ibadan, Southwest Nigeria: A Qualitative Study

Abstract: Background: Preconception care (PCC) is a recognised strategy for optimising maternal health and improving maternal and neonatal outcomes. Research has shown that PCC services are minimally available and yet to be fully integrated into maternal health services in Nigeria. This study explored the perceptions about PCC services among health care providers in Ibadan, Nigeria. Methods: This was a case study research among 26 health care providers -16 specialist physicians and nine nurses covering 10 specialties: O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…In this study, 92.5% (99) respondents had positive attitudes towards preconception care; they perceived it as a way of assisting in prevention of congenital abnormalities through early screening, testing and counselling. Similarly, in a study conducted by Ojifinni and Ibisomi [32] in Nigeria, it was reported that although all people of the reproductive age would benefit from preconception care, those who had medical problems such as hypertension, sickle cell disease, diabetes and infertility would benefit more. The study conducted in Nigeria further identified potential benefits of preconception care that included opportunity to prepare for pregnancy to ensure positive pregnancy outcomes.…”
Section: Attitudes Towards Preconception Carementioning
confidence: 99%
“…In this study, 92.5% (99) respondents had positive attitudes towards preconception care; they perceived it as a way of assisting in prevention of congenital abnormalities through early screening, testing and counselling. Similarly, in a study conducted by Ojifinni and Ibisomi [32] in Nigeria, it was reported that although all people of the reproductive age would benefit from preconception care, those who had medical problems such as hypertension, sickle cell disease, diabetes and infertility would benefit more. The study conducted in Nigeria further identified potential benefits of preconception care that included opportunity to prepare for pregnancy to ensure positive pregnancy outcomes.…”
Section: Attitudes Towards Preconception Carementioning
confidence: 99%